The Implementation of Green Housekeeping at Kampoeng Villa - Merta, Ketut Sami Ade; Armoni, Ni Luh Eka; Murni, Ni Nym Gst Suci; Septevany, Elvira (Sekolah Vokasi, Universitas Gadjah Mada, 2024)
This study aims to determine how the implementation of green housekeeping in Kampoeng Villa. This type of research is descriptive qualitative research. The data was collected by doing observation, interviews, and documentation. Sources of data used include primary and secondary data with a purposive sampling technique involving 6 sources. The results showed that Kampoeng Villa had implemented green housekeeping which was quite good, starting from the SOP that was already owned by Kampoeng Villa regarding the implementation of green housekeeping which was following the indicators in the study which included green action on changing linen which was carried out twice a week, changing towels every two days, use of cleaning materials that prioritize environmentally friendly products such as grated coconut, warm water and if needed only use a small amount of cleaning agent containing chemicals on particular objects, for the standard of cleanliness applied twice a week inside of the villa and every day outside the villa area. The ventilation in Kampoeng Villa was great due to they have comfortable building designs such as doors and windows that can be fully opened, which makes low consumption of air conditioning in each room, the air conditioners also have an inverter system that can be saving the energy cost. Kampoeng villas also used environmentally friendly products such as trash bins, guest supplies, and additional facilities, most of them made from the wood and ceramics. For waste management, Kampoeng Villa has collaborated with third parties in which organic and inorganic waste are placed in separate trash bins as well. The plastic or bottles, it is maximized as a place for some plants that can be placed inside and outside of the villa area refers to the 3R program, reuse, reduce and recycle. To maximize the implementation of green housekeeping, Kampoeng Villa has conducted intensive training for the employees and guests to participate and support its implementation. The employee also scheduled in writing, each employee working eight hours a day with three shift changes.